Salt tectonics, sediments and prospectivity - Alsop, G. I. (Geological Society, 2012)
Geoscientists from both industry and academia present a contemporary view of salt at a global scale. The studies examine the influence of salt on synkinematic sedimentation, its role in basin evolution and tectonics, and ultimately in hydrocarbon prospectivity. Recent improvements in seismic reflection, acquisition and processing techniques have led to significant advances in the understanding of salt and sediment interactions, both along the flanks of vertical or overturned salt margins, and in subsalt plays such as offshore Brazil.
Title from PDF title page (Lyell Collection, Special Publications, Geological Society of London Web site, viewed on Feb. 29, 2012).
Keywords: Salt tectonics.; Sedimentology.; elektronické knihy; electronic books